The role of pleurodesis in respiratory diseases. - Mercer, R; Hassan, M; Rahman, N (Taylor and Francis, 2018)
Introduction Pleurodesis is used to obliterate the pleural space, most commonly in patients with symptomatic malignant pleural effusions but also in patients with benign effusions or pneumothorax. Areas covered Traditionally, chemical pleurodesis has been undertaken at thoracoscopy or using instillation of a slurry through a chest drain. The optimum method of achieving pleurodesis, whether surgical or medical, has yet to be proven. Evidence in the different disease areas will be reviewed, along with ongoing trial evidence, which may change practice. Expert commentary Newer methods of achieving pleurodesis are being introduced. Studies have shown that instilling sclerosing agents via an indwelling pleural catheter or introducing drug-eluting catheters are safe and effective ways of inducing pleurodesis. There is evidence that pleurodesis might increase in survival, especially after pleural infection, possibly due to activation of the immune system. Multiple studies are currently underway to answer some of these questions and the future landscape may be very different from the present.